Gas exchange in ‘BRS Princesa’ banana (Musa spp.) under partial rootzone drying irrigation in the north of Minas Gerais, Brazil (2017)
This research aimed to evaluate physiological characteristics of 'BRS Princesa' banana under Partial Rootzone Drying irrigation, PRD. The five treatments, 1 - 50% of reduction in water depth (WD) with a frequency alternation of irrigation side (FA) of seven days during the whole production cycle; 2 - 50% of WD and FA of 14 days in the cycle; 3 - 50% of WD and FA of 21 days; 4 - 50% of WD with a fixed irrigation (only one lateral line on one side of the plant); and 5 - full irrigation (two lateral lines with open shutoff valve) throughout the cycle, they were arranged in a randomized block design with five replicates. There is a reduction in photosynthetic rates and water use efficiency as a result of enzymatic impairment or stomatal closure, due to the increased of leaf temperature. The stomatal conductance - gs was lower in plants irrigated with 50% of ETc with fixed irrigation in one side of the plant. Even with water deficit in the soil, using the PRD with 50% of ETc, Photosynthesis - A Transpiration - E; Leaf temperature - Tleaf, internal concentration of CO2 - Ci; stomatal conductance - gs; photosynthetically active radiation - Qleaf; carboxylation efficiency - A/Ci; Quantum efficiency of Photosynthesis - A/Qleaf; and instantaneous water use efficiency - WUE 'BRS Princesa' banana were similar among strategies, highlighting the possibility of use of the irrigation management technique with PRD, saving water, and no physiological changes in the plants.